Drug‐induced Apoptotic Neurodegeneration in the Developing Brain - Olney, John W. (Brain Pathol, 2006)
Physiological cell death (PCD), a process by which redundant or unsuccessful neurons are deleted by apoptosis (cell suicide) from the developing central nervous system, has been recognized as a natural phenomenon for many years. Whether environmental factors can interact with PCD mechanisms to increase the number of neurons undergoing PCD, thereby converting this natural phenomenon into a pathological process, is an interesting question for which new answers are just now becoming available. In a series of recent studies we have shown that 2 major classes of drugs (those that block NMDA glutamate receptors and those that promote GABAA receptor activation), when administered to immature rodents during the period of synaptogenesis, trigger widespread apoptotic neurodegeneration throughout the developing brain. In addition, we have found that ethanol, which has both NMDA antagonist and GABAmimetic properties, triggers a robust pattern of apoptotic neurodegeneration, thereby deleting large numbers of neurons from many different regions of the developing brain. These findings provide a more likely explanation than has heretofore been available for the reduced brain mass and lifelong neurobehavioral disturbances associated with the human fetal alcohol syndrome (FAS). The period of synaptogenesis, also known as the brain growth spurt period, occurs in different species at different times relative to birth. In rats and mice it is a postnatal event, but in humans it extends from the sixth month of gestation to several years after birth. Thus, there is a period in pre‐ and postnatal human development, lasting for several years, during which immature CNS neurons are prone to commit suicide if exposed to intoxicating concentrations of drugs with NMDA antagonist or GABAmimetic properties. These findings are important, not only because of their relevance to the FAS, but because there are many agents in the human environment, other than ethanol, that have NMDA antagonist or GABAmimetic properties. Such agents include drugs that may be abused by pregnant mothers (ethanol, phencyclidine [angel dust], ketamine [Special K], nitrous oxide [laughing gas], barbiturates, benzodiazepines), and many medicinals used in obstetric and pediatric neurology (anticonvulsants), and anesthesiology (all general anesthetics are either NMDA antagonists or GABAmimetics).